1992
DOI: 10.1073/pnas.89.16.7447
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal sodium pump distribution during renal tubulogenesis in congenital murine polycystic kidney disease.

Abstract: Congenital polycystic kidney disease is characterized by the formation of large fluid-filled cysts in kidney tubules. It has been postulated that increased epithelial cell proliferation and altered transtubular fluid transport are necessary for cyst formation. To address the latter problem, we have studied the plasma membrane distribution of the al and (31 subunits of Na+/K+-ATPase during progressive stages of proximal and collecting tubular cyst formation in the CPK mouse, a murine model of autosomal recessiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
39
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(42 citation statements)
references
References 38 publications
3
39
0
Order By: Relevance
“…It is well established that Na/K-ATPase normally polarizes to the basolateral membrane of fully differentiated mature collecting duct cells and is transiently expressed along the apical membrane of these nephron segments in fetal development (19) and murine models of ARPKD (8). However, it is unknown whether the apical pump, comprised of ␣1 and ␤2 subunits, is functional in these settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that Na/K-ATPase normally polarizes to the basolateral membrane of fully differentiated mature collecting duct cells and is transiently expressed along the apical membrane of these nephron segments in fetal development (19) and murine models of ARPKD (8). However, it is unknown whether the apical pump, comprised of ␣1 and ␤2 subunits, is functional in these settings.…”
Section: Discussionmentioning
confidence: 99%
“…Within this segment, Na diffuses from the urinary space into principal cells through apical epithelial Na channels (ENaC) and is extruded at the basolateral membrane in exchange for uptake of K by the Na/K-ATPase (11). Murine models of ARPKD exhibit apical immunodetectable Na/KATPase in cystic collecting ducts (8), suggesting that cystlining epithelial cells in ARPKD may secrete Na, as in AD-PKD. Few studies have systematically attempted to define the transport characteristics of ARPKD cystic renal epithelia.…”
mentioning
confidence: 99%
“…Avner et al (3) reported that the apical membrane Na ϩ -K ϩ -ATPase ␣1-subunit persisted in cystic kidneys of the PCK mouse, suggesting that its expression might be a manifestation of the relatively undifferentiated phenotype of the epithelial cells lining CD cysts. Although there is a difference in the abnormal expression pattern of the Na ϩ -K ϩ -ATPase ␣1-subunit in cystic epithelium between the PCK rat and CPK mouse models, these findings may suggest diversity of the peripheral phenotype of epithelial cells from the common pathophysiology of PKD.…”
Section: Discussionmentioning
confidence: 99%
“…Na + /K + ATPase in vertebrate epithelial tube-size disorders The Na + /K + ATPase has been implicated in vertebrate tubesize control by the abnormal subcellular localization of the Na + /K + ATPase in the inappropriately expanded tubules in individuals with PKD and in several animal models of cystic kidney diseases (Avner et al, 1992;Carone et al, 1995;Ogborn et al, 1995;Wilson et al, 2000;Wilson et al, 1991). However, it has not yet been determined whether this mislocalization contributes to the progression of cystic diseases or whether it is merely a secondary effect of other cellular defects.…”
Section: Septate Junction Control Of Tube Size Is Not Mediated By Parmentioning
confidence: 99%